Comparison of the behavioral responses induced by phenylalkylamine hallucinogens and their tetrahydrobenzodifuran ("FLY") and benzodifuran ("DragonFLY") analogs. (January 2019) - Halberstadt, Adam L.; Chatha, Muhammad; Stratford, Alexander; Grill, Matthias; Brandt, Simon D.
Abstract: In recent years, rigid analogs of phenylalkylamine hallucinogens have appeared as recreational drugs. Examples include 2-(8-bromo-2, 3, 6, 7-tetrahydrobenzo[1, 2- b :4, 5- b ′]difuran-4-yl)ethan-1-amine (2C-B-FLY) and 1-(8-bromobenzo[1, 2 -b ;4, 5 -b' ]difuran-4-yl)-2-aminopropane (Bromo-DragonFLY, DOB-DFLY). Although some rigid compounds such as DOB-DFLY reportedly have higher potency than their non-rigid counterparts, it is not clear whether the same is true for 2C-B-FLY and other tetrahydrobenzodifurans. In the present study, the head twitch response (HTR), a 5-HT2A receptor-mediated behavior induced by serotonergic hallucinogens, was used to assess the effects of 2, 5-dimethoxy-4-bromoamphetamine (DOB) and its α-desmethyl homologue 2, 5-dimethoxy-4-bromophenethylamine (2C-B), as well as their benzodifuranyl and tetrahydrobenzodifuranyl analogs, in C57BL/6J mice. DOB (ED50  = 0.75 μmol/kg) and 2C-B (ED50  = 2.43 μmol/kg) induced the HTR. The benzodifurans DOB-DFLY (ED50  = 0.20 μmol/kg) and 2C-B-DFLY (ED50  = 1.07 μmol/kg) had significantly higher potency than DOB and 2C-B, respectively. The tetrahydrobenzodifurans DOB-FLY (ED50  = 0.67 μmol/kg) and 2C-B-FLY (ED50  = 1.79 μmol/kg), by contrast, were approximately equipotent with their non-rigid counterparts. Three novel tetrahydrobenzodifurans (2C-I-FLY, 2C-E-FLY and 2C-EF-FLY) were also active in the HTR assay but had relatively low potency. In summary, the in vivo potency of 2, 5-dimethoxyphenylalkylamines is enhanced when the 2- and 5-methoxy groups are incorporated into aromatic furan rings, whereas potency is not altered if the methoxy groups are incorporated into dihydrofuran rings. The potency relationships for these compounds in mice closely parallel the human hallucinogenic data. The high potency of DOB-DFLY is probably linked to the presence of two structural features (a benzodifuran nucleus and an α-methyl group) known to enhance the potency of phenylalkylamine hallucinogens. Highlights: The hallucinogens 2C-B and DOB induced head twitches in mice. Tethering the methoxy groups into a benzodifuran nucleus increased potency. Tethering the methoxy groups into a tetrahydrobenzodifuran nucleus did not alter potency. The benzodifuran hallucinogen Bromo-DragonFLY was highly potent in mice.